European Transport System and the Tendencies in Its Development - Bakalova, Violeta; Makedonska, Violeta (Research Papers, 2008)
The proposed study considers the fundamental aspects of the European transport policy and more specifically, the problems involving a reduction in the harmful impact of transport on the environment and on the restructuring of the European transport system. The analysis is preceded by a research into different means of transportation – railway, water transport (sea, river and harbour), road and air transport. The tendencies in the development of each of those transport modes are outlined, with a focus on the development and on the improvement of railway, commercial marine navy and harbour activities. The tendencies in the transport development of European cities are outlined, more specifically, of passenger (subway, streetcar, car, etc.) and cargo transport. Pride of place is given to the problems of interaction between different kinds of transport and the development of combined transport.